The Politics Of Education In Indonesia In The Struggle Of Populist Promises And Budget Reality - Munandar, Aris; Susanti, Endang (Journal of Education and Learning Sciences, 2024)
Education policy in Indonesia has long been a battleground between populist promises and the constraints of the state budget. One of the latest policies, the free meal program for students, requires a substantial financial allocation. However, this comes at a time when the education sector is facing budget cuts, raising concerns about the sustainability and impact of such policies. This study aims to analyze the effects of populist education policies on budget allocation and the overall quality of education services in Indonesia. Using a qualitative approach based on policy analysis, this research examines how budget reductions affect educator welfare, learning facilities, and equitable access to education. While the free meal program is intended to enhance student well-being, the findings suggest that cuts in education funding could undermine efforts to improve teaching quality and exacerbate disparities in learning opportunities, particularly in underprivileged regions. The study highlights the trade-offs involved in implementing populist policies. While such initiatives can generate short-term political gains and address immediate concerns, they may compromise long-term educational development if not supported by a well-structured budget plan. A balanced approach is necessary—one that accommodates student welfare initiatives without sacrificing investments in teacher development, infrastructure, and curriculum enhancement. This study recommends that policymakers adopt a sustainable budget planning strategy that aligns with both populist goals and the long-term needs of the education sector. Only through careful financial management and evidence-based policy decisions can Indonesia ensure both student welfare and quality education services in the future.